BLOOD GLUCOSE, BLOOD PRESSURE AND HBA1C TO DIABETES MELITUS TYPE 2 - Dewi, Ratna (Indonesian Journal of Nursing Health Science, 2018)
Diabetes is the fourth leading cause of death in the world. Each year 3.2 people die from complications of diabetes. The purpose of this research is to know the relationship of blood glucose, HbA1C and blood pressure to type 2 diabetes mellitus at Jeruk Kebun Community Health Center. Descriptive analytic research method with cross sectional approach, sample size 42 people, chi-square statistical test. The results of the study were some clients of high blood pressure type 2 diabetes by 29 people (69%), most clients of low blood glucose level as many as 34 people (81%), most clients HBA1c high as 62 people (68.1%). . The result of statistic test in Linear Regression analysis shows that p value is 0,064 p <Î± (0,05). so it can be concluded that Blood Pressure, HBA1c, and Blood Glucose Level simultaneously did not affect the clients of type 2 diabetes mellitus at Kebun Jeruk Community Health Center. It is recommended for patients with type 2 diabetes is advised to perform blood glucose level checks, HBA1c because it helps proper medical treatment thereby reducing the risk of severe complications.Â Keywords: blood glucose, blood pressure, HBA1c diabetes mellitus type 2